Pengaruh Pemberian Edukasi Pra Anestesi Terhadap Tingkat Kecemasan Pada Pasien Laparatomy Dengan General Anestesi - Happy Nurhayati; Nabhani Nabhani; Adinda Thalia Amarra Septa (Jurnal Ilmu Kesehatan dan Gizi, 2023)
Background Surgical planning for preoperative patients is a psychosocial stressor that can cause stress, anxiety, and depression. Preoperative is the period before surgery is performed, starting from the time the decision is made for surgery until the patient is on the operating table. Laparotomy is one of the major surgical procedures by making an incision in the lining of the abdominal wall to obtain problems in the abdominal organs, such as cancer, bleeding, obstruction, and perforation. Research objectives: The general objective of this study was to determine the effect of implementing education on anxiety levels in preoperative apparatus patients with general anesthesia. Research methodology: This type of research is a quantitative study, with a quasy experimental research plan, with a non-randomized post-test one group design. . Results: It is known that the asymo.sig, (2-tailed) value is 0.000 <0.05. So it can be concluded that the "hypothesis is accepted". Thus it can be said that there are differences in the results of the intervention group and the control group. Because there is a significant difference, it is said that "there is an effect of providing education to preoperative laparotomy patients" Conclusion: Based on the results of the research and discussion that has been put forward under the title "the effect of providing pre-anesthesia education on anxiety levels in laparotomy patients with general anesthesia" it can be concluded as follows: There is a significant effect on providing education on preoperative anxiety of laparotomy with general anesthesia p = 0.000 (p <0.05) in the central surgical installation of Siti Fatimah Az-Zahra Hospital, South Sumatra Province.